Knowledge Attitude Practice study regarding Mosquitoes spreading Malaria and Dengue and their prevention in field practice area of Index Medical College Hospital Research Centre, Indore - Rashmi Bhujade; Aarti Sahasrabuddhe; V.K.Arora; Anil Singh Baghel (International Journal of Health and Clinical Research, 2021)
Background: Malaria and Dengue are two important mosquito borne diseases but in recent past the incidence of Malaria has decreased while Dengue incidence was increased. Reasons behind this contrast change in the incidence should be evaluated. Methods: Cross sectional community based study was conducted to evaluate the KAP regarding Malaria and Dengue spreading mosquito and their prevention on 515 participants.KAP level, difference in KAP regarding Malaria and Dengue spreading mosquito, association of socio-demographic factors with KAP and co relation of Knowledge with Attitude and practice were evaluated. Chi square test, paired t –test and co-relation test were applied for analysis. Results: Overall Knowledge, Attitude and Practices of participants regarding Malaria and Dengue spreading mosquitoes were low .Statistically significant better knowledge, Attitude and Practices scores were noted for Malaria spreading mosquitoes as compared to Dengue spreading mosquitoes. Occupation, Education, SES, and type of family were the important socio-demographic factors which were found to be significantly associated with Knowledge Attitude and Practices of participants. Positive co relation was found between Knowledge, Attitude and Practices. Conclusion: KAP regarding Malaria and Dengue spreading mosquitoes were not found satisfactory. Difference in bionomics and preventive measures for Malaria and Dengue spreading mosquitoes should be convey to public by health education. Socio-economic development, increase knowledge level of population can help in reducing the incidence of Malaria as well as Dengue.